Incidence, Risk Factors, and Outcomes of Thrombocytopenia in Older Medical Inpatients: A Prospective Cohort Study - Ioanna Papakitsou; Andria Papazachariou; Theodosios D Filippatos; Petros Ioannou (Hematology Reports)
Background: Thrombocytopenia, defined as a platelet count of less than 150 × 109/L, is a frequent condition among hospitalized patients and presents unique challenges in diagnosis and management. Despite its commonality, data on incidence and related risk factors in medical inpatients remain limited, especially in older people. Methods: A 2-year prospective cohort study with a 3-year follow-up was conducted on inpatients aged ≥65 years admitted to a medical ward. Clinical data were collected, including demographics, comorbidities, laboratory results, and outcomes. Multivariate logistic regression analysis assessed risk factors associated with non-resolution of thrombocytopenia and mortality. Results: The study included 961 older inpatients with a mean age of 82 years. Thrombocytopenia occurred in 22.6% of the study population. The most common causes were infections (57.4%) and drug-induced thrombocytopenia (25.3%). The non-resolution of thrombocytopenia was noted in 59% of patients. In-hospital and 3-year mortality was significantly higher in this subgroup compared to the rest (24.5% vs. 12.7%, p = 0.015) and (72.4% vs. 59.8%, p = 0.04, respectively). In multivariate analysis, nadir platelet count and hematologic disease were independent factors associated with the non-resolution of thrombocytopenia. Furthermore, in individuals with thrombocytopenia, the administration of norepinephrine (p < 0.001) and a higher clinical frailty score (p < 0.001) were observed as independent mortality predictors. Conclusions: Thrombocytopenia in older medical inpatients is associated with poor prognosis, particularly in those with non-resolution thrombocytopenia. Early identification and targeted management may improve outcomes.